The Impact of Citrus Bergamot Extract on Hemato- Biochemical, Inflammatory and Oxidative stress Parameters Induced by Acute Amikacin Toxicity in male Albino Rats - Ausama Ayob Jaccob; Fatima F. Dari; Muhsin S.G. AL-Moziel (College of Pharmacy University of Baghdad, 2023)
One of the most efficient aminoglycoside is amikacin. Yet, it has been linked to unwanted renal toxicity, which has resulted in negative alterations in various biochemical indicators, particularly those related to oxidative stress, kidney function, and inflammation. The goal of this research was to see how citrus bergamot extract affected hemato-biochemical, inflammatory, and oxidative stress parameters in male rats triggered by acute amikacin toxicity.A total of 30 male rats were divided into five equal groups, each with six rats. The first group received 1 ml DW orally and its represent control group. Group 1 was given 1 ml of DW orally and I.P. AK (1.2 gm/kg) on day seven. Group 2 was given 100 mg/kg CBE orally for ten days. Groups (3) and (4) were given 100 mg/kg and 200 mg/kg of CBE, respectively, orally for ten days. On the seventh day of the experiments, I.P. AK (1.2 gm/kg) was given to the test groups. At the end of the trial, blood samples were used to assess oxidative stress, renal function, inflammatory markers, and some hemato-biochemical parameters.Significantly higher levels of serum MDA, IL-6, urea, and creatinine, and an adversely affect lipid profile, are indications of AK-induced nephrotoxicity. Supplementation of CBE attenuated AK-induced change in these biomarkers.It was concluded that CBE supplementation protects against the nephrotoxic effects of AK because to its antioxidant, anti-inflammatory, and hypolipemic properties.